Relationship of Student's Vocabulary and Schematic Mastering with Observation Report Writing Skills - Eva Syamaria Subing; Fahrurrozi Fahrurrozi; Joko Sutrisno AB; Nani Angraini; Eny Dwi Marcela (IJLHE: International Journal of Language, Humanities, and Education, 2019)
The aim of this research was to explain how the relationship between vocabulary mastery and schemata on writing observational report skills. The data from this research is the main data obtained through giving assignments or tests, so that the results are in the form of quantitative descriptive data. Therefore, to find out the results, it is done using statistical calculations. From these calculations, it is known that there is a close relationship between vocabulary mastery and schemata with the skills of writing observation reports for class VII students of MTs N 2 Bandar Lampung in the 2018/2019 school year. Overall, it is concluded that students who are skilled in writing reports on observations have a close relationship with mastery of vocabulary and schemata.